STUDI FENOMENOLOGI FAKTOR PEMICU SERTA DAMPAK KEBAKARAN HUTAN DAN LAHAN DI KELURAHAN TELAWANG KECAMATAN BANJARMASIN BARAT KALIMANTAN SELATAN - Lailatus Isti Anah; Rosalina Kumalawati (Universitas Nusa Cendana, 2026)
Forest and land fires are a recurring environmental disaster in South Kalimantan that threaten ecosystems and community well-being. This study aims to identify the main causes of forest and land fires, examine the triggering factors, and examine their impacts on communities in Telawang District, West Banjarmasin Regency. A qualitative phenomenological approach was used to explore community experiences and perceptions related to fire incidents. Data were collected through semi-structured interviews with five purposively selected informants: the village head, a community leader, and three residents affected by the fires. Data were analyzed using the Miles and Huberman interactive model. The results indicate that human activity and low environmental awareness are considered the primary causes of forest and land fires, while climate factors play a secondary role. The most significant impact is respiratory health problems caused by smoke exposure. This study highlights the importance of strengthening environmental literacy, community participation, and government support to improve disaster mitigation and reduce fire-related risks.